Probing the W chromosome of the codling moth, Cydia pomonella, with sequences from microdissected sex chromatin - Fuková, Iva; Traut, Walther; Vítková, Magda; Nguyen, Petr; Kubícková, Svatava; Marec, Frantisek (Chromosoma, 2007)
The W chromosome of the codling moth, Cydia pomonella, like that of most Lepidoptera species, is heterochromatic and forms a female-specific sex chromatin body in somatic cells. We collected chromatin samples by laser microdissection from euchromatin and W-chromatin bodies. DNA from the samples was amplified by degenerate oligonucleotide-primed polymerase chain reaction (DOP-PCR) and used to prepare painting probes and start an analysis of the W-chromosome sequence composition. With fluorescence in situ hybridization (FISH), the euchromatin probe labelled all chromosomes, whereas the W-chromatin DNA proved to be a highly specific W-chromosome painting probe. For sequence analysis, DOP-PCR-generated DNA fragments were cloned, sequenced, and tested by Southern hybridization. We recovered single-copy and low-copy W-specific sequences, a sequence that was located only in the W and the Z chromosome, multi-copy sequences that were enriched in the W chromosome but occurred also elsewhere, and ubiquitous multi-copy sequences. Three of the multi-copy sequences were recognized as derived from hitherto unknown retrotransposons. The results show that our approach is feasible and that the W-chromosome composition of C. pomonella is not principally different from that of Bombyx mori or from that of Y chromosomes of several species with an XY sex-determining mechanism. The W chromosome has attracted repetitive sequences during evolution but also contains unique sequences.
Keywords: Moths; druhová specificita; sekvence nukleotidů; Sex Chromosomes; polymerázová řetězová reakce; pohlavní chromozomy; hybridizace in situ fluorescenční; můry; Molecular Probes; Chromosome Painting; mikrodisekce; Southernův blotting; Sequence Analysis, DNA; sekvenční analýza DNA; molekulární sekvence - údaje; Sex Chromatin; DNA Primers; Species Specificity; Microdissection; Animals; sexchromatin; zvířata; molekulární sondy; DNA primery; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Polymerase Chain Reaction; Base Sequence; Oligonucleotides; Blotting, Southern; oligonukleotidy; malování chromozomů